Continuing medical education in Serbia with particular reference to the Faculty of Medicine, Belgrade - Bjegović-Mikanović, Vesna; Lalić, Nebojša; Wenzel, Helmut; Nikolić-Mandić, Ružica; Laaser, Ulrich (Vojnosanitetski pregled, 2015)
Background/Aim. Continuing Medical Education (CME), conceptualised as lifelong learning (LLL) aims at improving human resources and continuing professional development. Various documents of European institutions underline its key importance. This paper therefore tries to analyse the current status of CME and the main deficits in the delivery of LLL courses at medical faculties in Serbia with special consideration of the Faculty of Medicine in Belgrade with detailed financial data available. Methods. Data of 2,265 medical courses submitted in 2011 and 2012 for accreditation were made available, thereof 403 courses submitted by 4 medical faculties in Serbia (Belgrade, Kragujevac, Niš, Novi Sad). A subset of more detailed information on 88 delivered courses with 5,600 participants has been provided by the Faculty of Medicine, Belgrade. All data were transferred into an Excel file and analysed with XLSTAT 2009. To reduce the complexity and possible redundancy we performed a principal component analysis (PCA). Correlated component regression (CCR) models were used to identify determinants of course participation. Results. During the 2-year period 12.9% of all courses were submitted on pre-clinical and 62.4% on clinical topics, 12.2% on public health, while 61.5% of all took place in Belgrade. The subset of the Faculty of Medicine, Belgrade comprised 3,471 participants registered with 51 courses accredited and delivered in 2011 and 2,129 participants with 37 courses accredited and delivered in 2012. The median number of participants per course for the entire period was 45; the median fee rates for participants were 5,000 dinars in 2011 and 8,000 in 2012, resulting together with donations in a total income for both years together of 16,126,495.00 dinar or almost 144,000.00 euro. This allowed for a median payment of approximately 90 eur per hour lectured in 2011 and 49 euro in 2012. The 2 factors, D1 (performance) and D2 (attractiveness), identified in the PCA for Medical Faculties in Serbia, explain 71.8% of the variance. Most relevant are the duration of the courses, credit points, and hours per credit point gained by lecturers and participants respectively. In the PCA for Belgrade D1 and D2 explain 40.7% of the total variance. The CCR on the number of participants reveals the highest positive impact from the number of lecturers per course and the expenditure on amenities, the highest negative impact from the total income collected per participant. Conclusion. The faculties of medicine in Serbia should reconsider the entire structure of their organisation of CME, especially to improve the quantity and quality of registration limit the course fee rates per hour and reduce administrative and other costs request lecturing in CME programmes as obligatory for academic promotion and organise a focussed marketing.